2016
DOI: 10.1021/acs.jctc.5b00934
|View full text |Cite
|
Sign up to set email alerts
|

Using MD Simulations To Calculate How Solvents Modulate Solubility

Abstract: Here, our interest is in predicting solubility in general, and we focus particularly on predicting how the solubility of particular solutes is modulated by the solvent environment. Solubility in general is extremely important, both for theoretical reasons – it provides an important probe of the balance between solute-solute and solute-solvent interactions – and for more practical reasons, such as how to control the solubility of a given solute via modulation of its environment, as in process chemistry and sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 62 publications
(148 reference statements)
2
45
0
Order By: Relevance
“…Additionally, only a limited number of neutral solutes have their solvation free energies measured in multiple solvents. These difficulties in the curating of solvation free energies for force field evaluation are well known and have led to the use of alternate metrics with more abundant experimental data, such as solubility or distribution coefficient calculations, in recent tests 73, 74. These metrics provide promising ways of evaluating multiple protocols in blind tests, but, as demonstrated here, there remains a role for computationally more straightforward absolute free energy calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only a limited number of neutral solutes have their solvation free energies measured in multiple solvents. These difficulties in the curating of solvation free energies for force field evaluation are well known and have led to the use of alternate metrics with more abundant experimental data, such as solubility or distribution coefficient calculations, in recent tests 73, 74. These metrics provide promising ways of evaluating multiple protocols in blind tests, but, as demonstrated here, there remains a role for computationally more straightforward absolute free energy calculations.…”
Section: Discussionmentioning
confidence: 99%
“…For saturated solutions of solid solutes the need to calculate the residual chemical potential of the solid hampers the use of molecular simulations [58]. However, molecular dynamics simulations can straightforwardly be used to calculate relative solubilities for the same solute in different solvents [20]. Therefore, we conclude that molecular dynamics simulations with recent force fields will gain an increasing importance in predicting solubilities in complex systems.…”
Section: Aqueous Solubility Of N-alkanes and Primary Alcoholsmentioning
confidence: 97%
“…For drug-like or polyfunctional molecules which are often of interest for simulation studies few experimental data exist on the solvation free energy, a quantity, which is often used as target property in force field parametrization and validation [16 -19]. In contrast data on solubility are often more abundant, making the calculation of solubilities -even relative solubilities -particularly important [20].…”
Section: Introductionmentioning
confidence: 99%
“…This computation method has been successfully used to predict hydration free energies of a variety of compounds at different temperatures 14,17,18 . The resulting free energies were close to those obtained with thermodynamic integration, at minimal computational cost.…”
Section: Solutes and Solvationmentioning
confidence: 99%
“…A few studies that have shown promising results relied on specifically parametrized force fields, which in general require a lot of effort to develop [14][15][16] .…”
mentioning
confidence: 99%